2005
DOI: 10.1007/s10447-005-2256-9
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Teaching Prevention and Developmental Issues Among Turkish Counselor Educators

Abstract: The goal of this study was to determine existing attitudes of Turkish counselor educators regarding the need to emphasize prevention and developmental issues in counselor education programs and to propose ways of incorporating these functions into the counseling area as necessary. Data were collected via questionnaire from 104 counselor educators who have been working at Turkish universities. Of the 50 professors, 23 instructors and 31 research assistants who responded, 36 had prior school counselor experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Counselor educators in Korkut's (2005) study reported that they did not place much emphasis on prevention or developmental issues in their courses. Skills development also seems to be a neglected aspect of counselor education.…”
Section: Counselor Educationmentioning
confidence: 93%
See 3 more Smart Citations
“…Counselor educators in Korkut's (2005) study reported that they did not place much emphasis on prevention or developmental issues in their courses. Skills development also seems to be a neglected aspect of counselor education.…”
Section: Counselor Educationmentioning
confidence: 93%
“…In recent years, there has been an emphasis on the preventive and developmental approaches in counseling (Korkut, 2005). Both of these are reflected in the 2001 MONE Guidance and Psychological Counseling Services Regulation, which emphasizes the use of the preventive and developmental approaches in school counseling.…”
Section: Major Developments Of Turkish Counselingmentioning
confidence: 99%
See 2 more Smart Citations